A gel polymer composite electrolyte and preparation method thereof and secondary lithium battery

By cross-linking and polymerizing pure acrylate and modified acrylate polymers on the nanofiber skeleton to form gel polymer composite electrolytes, the safety risks and lithium dendrites present in traditional lithium-ion batteries at high temperatures are solved, and higher conductivity and battery life are achieved.

CN119742437APending Publication Date: 2025-04-01APOWER ELECTRONICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411910351.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Traditional lithium-ion batteries have safety risks, such as side reactions of electrolytes, interface instability and lithium dendrites growth, and the diaphragm may lead to heat shrinkage and short circuit risks at high temperatures.

Method used

The nanofiber skeleton is used as the main body, and the pure acrylate polymer and the modified acrylate polymer are crosslinked thereon to form a gel polymer composite electrolyte. The electrolyte inhibits the generation of lithium dendrites through halogen-containing and nitrogen-containing acrylate polymers, thereby increasing the conductivity and the migration number of lithium ions.

Benefits of technology

It improves the battery's high-voltage resistance, thermal stability, interface compatibility and mechanical properties, generates a stable electrode/electrolyte interface, extends the battery life, and reduces the generation of lithium dendrites, improves the conductivity and the migration number of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205490380000161
    Figure BDA0005205490380000161
  • Figure BDA0005205490380000171
    Figure BDA0005205490380000171
Patent Text Reader

Abstract

The present invention provides a gel polymer composite electrolyte, a preparation method thereof and a secondary lithium battery. The gel polymer composite electrolyte comprises a nanofiber skeleton, an electrolyte containing a lithium salt, an acrylate polymer and a modified acrylate polymer; wherein the modified acrylate polymer is a combination of a halogen-containing acrylate polymer and a nitrogen-containing acrylate polymer. The present invention takes a nanofiber skeleton as the main body, cross-links and polymerizes acrylate polymers and modified acrylate polymers on the skeleton, thereby improving the high-voltage resistance of the gel polymer composite electrolyte, improving thermal stability, interface compatibility and mechanical properties, generating a stable electrode / electrolyte interface and improving battery life. In addition, the halogen-containing acrylate polymer and the nitrogen-containing acrylate polymer are conducive to the formation of lithium halide and lithium nitride on the electrolyte surface, thereby inhibiting the generation of lithium dendrites and improving the conductivity and the migration number of lithium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a gel polymer composite electrolyte and a preparation method thereof, and a secondary lithium battery. Background Art

[0002] Traditional lithium-ion batteries using liquid electrolytes have potential safety risks, such as serious electrolyte side reactions, unstable interface layers and lithium dendrite growth. At the same time, there is also the risk of battery leakage, gas production, and even fire at high temperatures.

[0003] Most lithium-ion batteries use polypropylene and polyethylene separators. These two separators have excellent mechanical properties, but insufficient thermal stability. They may shrink thermally in high temperature environments, increasing the risk of internal short circuits in the battery. At the same time, their wettability to electrolytes is average.

[0004] Polymer solid electrolytes are highly processable and can be prepared into flexible thin-film batteries with certain mechanical strength. At the same time, they are highly stable to lithium and have good battery cycle performance. However, they have low ionic conductivity at room temperature and have high process requirements.

[0005] Therefore, it is urgent to develop a gel polymer electrolyte with high voltage resistance, thermal stability, interfacial compatibility and excellent electrochemical properties. Summary of the invention

[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a gel polymer composite electrolyte and a preparation method thereof and a secondary lithium battery. The present invention takes a nanofiber skeleton as the main body, and cross-links and polymerizes pure acrylate polymer and modified acrylate polymer on the skeleton, thereby improving the high voltage resistance of the gel polymer composite electrolyte, improving thermal stability, interface compatibility and mechanical properties, and generating a stable electrode / electrolyte interface, thereby improving battery life. In addition, halogen-containing acrylate polymers and nitrogen-containing acrylate polymers are conducive to the formation of lithium halide and lithium nitride on the electrolyte surface, thereby inhibiting the generation of lithium dendrites and improving conductivity and the migration number of lithium ions.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a gel polymer composite electrolyte, which comprises a nanofiber skeleton, an electrolyte containing a lithium salt, a pure acrylate polymer and a modified acrylate polymer.

[0009] Wherein, the modified acrylic ester polymer is a combination of a halogen-containing acrylic ester polymer and a nitrogen-containing acrylic ester polymer.

[0010] The present invention uses a nanofiber skeleton as the main body, and cross-links and polymerizes acrylate polymers and modified acrylate polymers on the skeleton, thereby improving the high-voltage resistance of the gel polymer composite electrolyte, improving thermal stability, interface compatibility and mechanical properties, and generating a stable electrode / electrolyte interface to increase battery life. In addition, the halogen-containing acrylate polymer and the nitrogen-containing acrylate polymer are conducive to the formation of lithium halide and lithium nitride on the electrolyte surface, thereby inhibiting the generation of lithium dendrites and improving the conductivity and the migration number of lithium ions.

[0011] In the present invention, halogen-containing acrylate polymers and nitrogen-containing acrylate polymers are used as modified acrylate polymers. The introduction of the above combination is beneficial to the production of lithium halide and lithium nitride on the surface. The addition of lithium halide can form a uniform and stable lithium ion transmission channel at the interface, effectively reducing the interface resistance, while the inorganic lithium nitride component can promote ion transmission between the electrolyte and the lithium metal negative electrode, improve the mechanical properties of the film, reduce the nucleation overpotential, and ultimately inhibit the growth of lithium dendrites.

[0012] In the present invention, pure acrylate polymer refers to unmodified acrylate polymer.

[0013] Preferably, the material of the nanofiber skeleton includes any one or a combination of at least two of polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), polyethylene oxide (PEO) or silicon dioxide (SiO2), preferably polyacrylonitrile.

[0014] Preferably, the thickness of the nanofiber skeleton is 20-100 μm, for example, 20 μm, 40 μm, 60 μm, 80 μm or 100 μm.

[0015] Preferably, in the lithium salt-containing electrolyte, the lithium salt includes any one of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate or lithium dioxalatoborate, or a combination of at least two thereof.

[0016] Preferably, in the electrolyte containing lithium salt, the solvent includes any one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC) or ethyl methyl carbonate (EMC), or a combination of at least two thereof.

[0017] Preferably, the pure acrylate polymer includes any one or a combination of at least two of polyethylene glycol diacrylate, bisphenol A ethoxylated acid diacrylate polymer, dipentaerythritol pentaacrylate polymer, methacrylate polyethylene glycol methacrylate, polydipentaerythritol hexaacrylate or bisphenol A propylene glycol dimethacrylate polymer, preferably any one or a combination of at least two of polyethylene glycol diacrylate, bisphenol A ethoxylated acid diacrylate polymer or dipentaerythritol pentaacrylate polymer.

[0018] In the present invention, the combination of the above-mentioned pure acrylate polymer and modified acrylate polymer is used, which helps to improve the conductivity and ion migration number of the gel polymer composite electrolyte, enhance the high voltage resistance and improve the battery performance through mutual cross-linking polymerization.

[0019] Preferably, the mass ratio of the pure acrylate polymer to the modified acrylate polymer is (60-99):(1-40), wherein the selection range of the pure acrylate polymer "60-99" can be, for example, 60, 70, 80, 90, 95 or 99, and the selection range of the modified acrylate polymer "1-40" can be, for example, 1, 10, 20, 30 or 40, preferably (70-95):(5-30).

[0020] In the present invention, if the mass ratio of pure acrylate polymer to modified acrylate polymer is too small, that is, the modified acrylate polymer is too much, not only will the overall water resistance of the polymer decrease, but it may also fail to polymerize. This is mainly because the electronegativity of halogen atoms is relatively high, which may weaken the interaction between polymer chains; if the mass ratio of pure acrylate polymer to modified acrylate polymer is too large, that is, the modified acrylate polymer is too little, it may lead to insufficient crosslinking reaction, resulting in a decrease in the degree of crosslinking, which will affect the mechanical strength, heat resistance and solvent resistance of the polymer.

[0021] Preferably, the halogen-containing acrylate polymer includes a fluorine-containing acrylate polymer and / or a bromine-containing acrylate polymer.

[0022] In the present invention, the role of the halogen-containing acrylic polymer is to improve the conductivity and the migration number of lithium ions, induce the formation of a SEI mixed with multiple lithium halides on the surface of the lithium metal negative electrode, and reduce the side reaction between the electrode and the solvent or salt.

[0023] Preferably, the fluorine-containing acrylate polymer includes any one of 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate, (perfluorocyclohexyl) methacrylate, 2-(perfluorooctyl) ethyl methacrylate, 1H,1H,11H-perfluoroundecyl methacrylate, 2,2,3,3,3-pentafluoropropyl acrylate or 2,2,3,3,4,4,4-heptafluorobutyl methacrylate, or a combination of at least two thereof.

[0024] Preferably, the bromine-containing acrylate polymer comprises poly(pentabromobenzyl acrylate).

[0025] Preferably, the nitrogen-containing acrylate polymer comprises ethyl α-cyano-β-(2-furyl)acrylate.

[0026] Preferably, the mass ratio of the halogen-containing acrylate polymer to the nitrogen-containing acrylate polymer is (50-95):(5-50), wherein the selection range of the halogen-containing acrylate polymer "50-95" can be, for example, 50, 60, 70, 80, 90 or 95, and the selection range of the nitrogen-containing acrylate polymer "5-50" can be, for example, 5, 10, 20, 30, 40 or 50, preferably (70-90):(10-30).

[0027] In the present invention, if the mass ratio of the halogen-containing acrylate polymer to the nitrogen-containing acrylate polymer is too small, that is, the amount of the nitrogen-containing acrylate polymer is too much, the excessive nitrogen-containing functional groups may react with the lithium salt in the electrolyte to generate compounds insoluble in the electrolyte, thereby affecting the ion conductivity of the electrolyte, and the amide bonds or other nitrogen-containing functional groups formed in the polymer chain will affect the overall rigidity of the polymer; if the mass ratio of the halogen-containing acrylate polymer to the nitrogen-containing acrylate polymer is too large, that is, the amount of the nitrogen-containing acrylate polymer is too little, the toughness and ionic conductivity of the SEI layer will be reduced, and the uniformity of lithium deposition will deteriorate.

[0028] Preferably, based on the total weight of the gel polymer composite electrolyte being 100%, the weight fraction of the lithium salt-containing electrolyte is 50-99%, for example, it can be 50%, 60%, 70%, 80%, 90%, 95% or 99%, etc., preferably 70-95%.

[0029] Preferably, based on the total weight of the gel polymer composite electrolyte being 100%, the total weight fraction of the acrylate polymer and the modified acrylate polymer is 1-50%, for example, 1%, 10%, 20%, 30%, 40% or 50%, etc., preferably 5-30%.

[0030] In the present invention, if the total amount of the acrylate polymer and the modified acrylate polymer is too much, the amount of the lithium salt-containing electrolyte is too little, which will lead to insufficient ion transmission channels, thereby hindering the normal migration of lithium ions and directly affecting the cycle performance of the battery; if the total amount of the acrylate polymer and the modified acrylate polymer is too little, it may be impossible to form a condensed electrolyte, and the internal electrolyte cannot be locked and still flows.

[0031] In a second aspect, the present invention provides a method for preparing the gel polymer composite electrolyte as described in the first aspect, the preparation method comprising the following steps:

[0032] (a) A lithium salt-containing electrolyte, a pure acrylate polymer, a modified acrylate polymer and an initiator are mixed to obtain a prepolymerization solution.

[0033] (b) mixing the prepolymer solution and the nanofiber skeleton, and performing an in-situ polymerization reaction to obtain the gel polymer composite electrolyte.

[0034] Preferably, the concentration of the lithium salt-containing electrolyte in step (a) is 0.5-2 mol / L, for example, 0.5 mol / L, 1 mol / L, 1.5 mol / L or 2 mol / L.

[0035] Preferably, the initiator in step (a) comprises any one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile or dimethyl azobisisobutyrate or a combination of at least two thereof, preferably azobisisobutyronitrile.

[0036] Preferably, based on the total weight of the pure acrylate polymer and the modified acrylate polymer being 100%, the weight fraction of the initiator is 0.2-1.2%, for example, 0.2%, 0.5%, 1% or 1.2%.

[0037] Preferably, the mixing process in step (a) is accompanied by stirring.

[0038] Preferably, the method for preparing the nanofiber skeleton in step (b) comprises electrospinning.

[0039] Preferably, in the electrospinning method, the weight ratio of the solute in the electrospinning solution to the solvent is 5-15%, for example, 5%, 10% or 15%, etc., preferably 10%.

[0040] The present invention does not limit the type of solvent for the electrospinning solution. For example, it may be N-methylformamide, N-methylacetamide or N-methylpyrrolidone.

[0041] Preferably, the specific parameters of the electrospinning method include:

[0042] The distance between the spinneret and the grounded collector is 15-25 cm, for example, 15 cm, 20 cm or 25 cm, etc., the applied voltage is 10-25 KV, for example, 10 KV, 15 KV, 20 KV or 25 KV, etc., and the feed rate of the electrospinning solution is 0.3-0.8 mm / h, for example, 0.3 mm / h, 0.4 mm / h, 0.5 mm / h, 0.6 mm / h, 0.7 mm / h or 0.8 mm / h, etc.

[0043] The present invention utilizes the electrostatic spinning method and can prepare an ideal thickness of the nanofiber skeleton by adjusting the above parameters.

[0044] Preferably, the temperature of the in-situ polymerization in step (b) is 50-70°C, for example, 50°C, 60°C or 70°C, and the time is 6-15h, for example, 6h, 8h, 10h, 11h, 12h, 13h, 14 or 15h.

[0045] Preferably, the preparation method comprises the following steps:

[0046] (1) A flexible nanofiber skeleton with a thickness of 20-100 μm is prepared as a base membrane by an electrospinning method, and the specific parameters include:

[0047] The distance between the spinneret and the grounded collector was 15-25 cm, the applied voltage was 10-25 KV, and the feed rate of the electrospinning solution was 0.3-0.8 mm / h.

[0048] (2) Under stirring conditions, pure acrylate polymer and modified acrylate polymer are added to an electrolyte containing lithium salt to obtain a mixed solution, and then an initiator is added, and stirring is continued to obtain a prepolymerization solution, wherein the mass fraction of the initiator is 0.2-1.2% based on the total weight of the pure acrylate polymer and the modified acrylate polymer as 100%; the mass ratio of the pure acrylate polymer to the modified acrylate polymer is (60-99):(1-40).

[0049] (3) adding the prepolymer solution dropwise to the flexible nanofiber skeleton in step (1) to wet it, and then placing it at 50-70° C. for 6-15 hours to carry out an in-situ polymerization reaction to obtain the gel polymer composite electrolyte.

[0050] In a third aspect, the present invention provides a secondary lithium battery, wherein the secondary lithium battery comprises the gel polymer composite electrolyte as described in the first aspect.

[0051] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The present invention uses a nanofiber skeleton as the main body, and cross-links and polymerizes pure acrylate polymer and modified acrylate polymer on the skeleton, thereby improving the high-voltage resistance of the gel polymer composite electrolyte, improving the thermal stability, interface compatibility and mechanical properties, and generating a stable electrode / electrolyte interface, thereby improving the battery life.

[0054] (2) In the present invention, the halogen-containing acrylate polymer and the nitrogen-containing acrylate polymer are used in coordination, which is beneficial to the formation of lithium halide and lithium nitride on the electrolyte surface, thereby inhibiting the generation of lithium dendrites and improving the conductivity and the migration number of lithium ions. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] Example 1

[0057] This embodiment provides a gel polymer composite electrolyte, which includes a flexible PAN nanofiber skeleton, an electrolyte containing a lithium salt, a pure acrylate polymer, and a modified acrylate polymer.

[0058] The thickness of the flexible PAN nanofiber skeleton is 50 μm, and the nanofiber skeleton includes fibers with a diameter of 16 mm; the concentration of the lithium salt-containing electrolyte is 1.0 mol / L, the lithium salt is lithium hexafluorophosphate, and the solvent includes diethyl carbonate and ethylene carbonate in a volume ratio of 1:1.

[0059] The pure acrylate polymer is polyethylene glycol diacrylate, the modified acrylate polymer is a combination of a fluorine-containing acrylate polymer and a nitrogen-containing acrylate polymer, the fluorine-containing acrylate polymer is 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate, and the nitrogen-containing acrylate polymer is ethyl α-cyano-β-(2-furanyl) acrylate; the mass ratio of the pure acrylate polymer to the modified acrylate polymer is 90:10, and the mass ratio of the fluorine-containing acrylate polymer to the nitrogen-containing acrylate polymer is 80:20; based on the total weight of the gel polymer composite electrolyte being 100%, the weight fraction of the lithium salt-containing electrolyte is 85%, and the total weight fraction of the pure acrylate polymer and the modified acrylate polymer is 15%.

[0060] This embodiment also provides a method for preparing the above-mentioned gel polymer composite electrolyte, and the preparation method comprises the following steps:

[0061] (1) A PAN solution was prepared, wherein the weight ratio of PAN to N-methylformamide was 10%, and a flexible PAN nanofiber skeleton with a thickness of 50 μm was prepared as a base film by an electrospinning method. The specific parameters included:

[0062] The distance between the spinneret and the grounded collector was 17 cm, the applied voltage was 19 KV, and the feed rate of the electrospinning solution was 0.5 mm / h.

[0063] (2) In a glove box protected by argon gas and with a water content and an oxygen content both less than 1 ppm, an electrolyte containing a lithium salt with a concentration of 1 mol / L was prepared.

[0064] Under stirring conditions, polyethylene glycol diacrylate, 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate and ethyl α-cyano-β-(2-furyl) acrylate are added to a lithium salt-containing electrolyte to obtain a mixed solution, and then an AIBN initiator is added and stirring is continued to obtain a prepolymer solution.

[0065] Wherein, based on the total weight of polyethylene glycol diacrylate, 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate and ethyl α-cyano-β-(2-furyl) acrylate being 100%, the mass fraction of the AIBN initiator is 0.5%.

[0066] (3) The prepolymer solution is added dropwise onto the flexible PAN nanofiber skeleton described in step (1) to soak it, and then a lithium iron phosphate positive electrode, a lithium negative electrode and the flexible PAN nanofiber skeleton soaked with the prepolymer solution are assembled into a liquid battery, the liquid battery is allowed to stand at room temperature of 25°C for 12 hours, and then an in-situ polymerization reaction is carried out at 60°C for 12 hours to obtain a lithium-ion battery, wherein the lithium-ion battery has a gel polymer composite electrolyte.

[0067] Example 2

[0068] This embodiment provides a gel polymer composite electrolyte, which includes a flexible PAN nanofiber skeleton, an electrolyte containing a lithium salt, a pure acrylate polymer, and a modified acrylate polymer.

[0069] The thickness of the flexible PAN nanofiber skeleton is 50 μm, and the nanofiber skeleton includes fibers with a diameter of 16 mm; the concentration of the lithium salt-containing electrolyte is 1.0 mol / L, the lithium salt is lithium hexafluorophosphate, and the solvent includes diethyl carbonate and ethylene carbonate in a volume ratio of 1:1.

[0070] The pure acrylate polymer is bisphenol A ethoxylated diacrylate, the modified acrylate polymer is a combination of a bromine-containing acrylate polymer and a nitrogen-containing acrylate polymer, the bromine-containing acrylate polymer is poly(pentabromobenzyl acrylate), and the nitrogen-containing acrylate polymer is ethyl α-cyano-β-(2-furyl) acrylate; the mass ratio of the pure acrylate polymer to the modified acrylate polymer is 90:10; the mass ratio of the bromine-containing acrylate polymer to the nitrogen-containing acrylate polymer is 80:20; based on the total weight of the gel polymer composite electrolyte being 100%, the weight fraction of the lithium salt-containing electrolyte is 85%, and the total weight fraction of the pure acrylate polymer and the modified acrylate polymer is 15%.

[0071] This embodiment also provides a method for preparing the above-mentioned gel polymer composite electrolyte, and the preparation method comprises the following steps:

[0072] (1) A PAN solution was prepared, wherein the weight ratio of PAN to N-methylformamide was 10%, and a flexible PAN nanofiber skeleton with a thickness of 50 μm was prepared as a base film by an electrospinning method. The specific parameters included:

[0073] The distance between the spinneret and the grounded collector was 17 cm, the applied voltage was 19 KV, and the feed rate of the electrospinning solution was 0.5 mm / h.

[0074] (2) In a glove box protected by argon gas and with a water content and an oxygen content both less than 1 ppm, an electrolyte containing a lithium salt with a concentration of 1 mol / L was prepared.

[0075] Under stirring conditions, bisphenol A ethoxylated diacrylate, poly (pentabromobenzyl acrylate) and ethyl α-cyano-β-(2-furyl) acrylate are added to a lithium salt-containing electrolyte to obtain a mixed solution, and then an AIBN initiator is added and stirring is continued to obtain a prepolymer solution.

[0076] Wherein, based on the total weight of bisphenol A ethoxylated diacrylate, 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate and ethyl α-cyano-β-(2-furyl) acrylate being 100%, the mass fraction of the AIBN initiator is 0.5%.

[0077] (3) The prepolymer solution is added dropwise onto the flexible PAN nanofiber skeleton described in step (1) to soak it, and then a lithium iron phosphate positive electrode, a lithium negative electrode and the flexible PAN nanofiber skeleton soaked with the prepolymer solution are assembled into a liquid battery, and the liquid battery is allowed to stand at room temperature of 25°C for 12 hours, and then an in-situ polymerization reaction is carried out at 60°C for 12 hours to obtain a lithium-ion battery having a gel polymer composite electrolyte.

[0078] Example 3

[0079] This embodiment provides a gel polymer composite electrolyte, which includes a flexible PAN nanofiber skeleton, an electrolyte containing a lithium salt, a pure acrylate polymer, and a modified acrylate polymer.

[0080] The thickness of the flexible PAN nanofiber skeleton is 50 μm, and the nanofiber skeleton includes fibers with a diameter of 16 mm; the concentration of the lithium salt-containing electrolyte is 1.0 mol / L, the lithium salt is lithium hexafluorophosphate, and the solvent includes diethyl carbonate and ethylene carbonate in a volume ratio of 1:1.

[0081] The pure acrylate polymer is dipentaerythritol pentaacrylate, the modified acrylate polymer is a fluorine-containing acrylate polymer and a nitrogen-containing acrylate polymer, the fluorine-containing acrylate polymer is 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate, and the nitrogen-containing acrylate polymer is ethyl α-cyano-β-(2-furanyl) acrylate; the mass ratio of the pure acrylate polymer and the modified acrylate polymer is 90:10, and the mass ratio of the fluorine-containing acrylate polymer and the nitrogen-containing acrylate polymer is 80:20; based on the total weight of the gel polymer composite electrolyte being 100%, the weight fraction of the lithium salt-containing electrolyte is 85%, and the total weight fraction of the pure acrylate polymer and the modified acrylate polymer is 15%. This embodiment also provides a preparation method for the above-mentioned gel polymer composite electrolyte, and the preparation method comprises the following steps:

[0082] (1) A PAN solution was prepared, wherein the weight ratio of PAN to N-methylformamide was 10%, and a flexible PAN nanofiber skeleton with a thickness of 50 μm was prepared as a base film by an electrospinning method. The specific parameters included:

[0083] The distance between the spinneret and the grounded collector was 17 cm, the applied voltage was 19 KV, and the feed rate of the electrospinning solution was 0.5 mm / h.

[0084] (2) In a glove box protected by argon gas and with a water content and an oxygen content both less than 1 ppm, an electrolyte containing a lithium salt with a concentration of 1 mol / L was prepared.

[0085] Under stirring conditions, dipentaerythritol pentaacrylate, 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate and ethyl α-cyano-β-(2-furyl) acrylate are added to a lithium salt-containing electrolyte to obtain a mixed solution, and then an AIBN initiator is added and stirring is continued to obtain a prepolymer solution.

[0086] Wherein, based on the total weight of dipentaerythritol pentaacrylate, 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate and ethyl α-cyano-β-(2-furyl) acrylate being 100%, the mass fraction of the AIBN initiator is 0.5%.

[0087] (3) adding the prepolymer solution dropwise onto the flexible PAN nanofiber skeleton described in step (1) to wet it, and then assembling lithium iron phosphate (positive electrode, lithium negative electrode) and the flexible PAN nanofiber skeleton wetted with the prepolymer solution into a liquid battery, leaving the liquid battery at room temperature of 25°C for 12 hours, and then performing an in-situ polymerization reaction at 60°C for 12 hours to obtain a lithium ion battery, wherein the lithium ion battery has a gel polymer composite electrolyte.

[0088] Example 4

[0089] The difference between this embodiment and embodiment 3 is that 3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate is replaced by 2,2,3,3,3-pentafluoropropyl acrylate.

[0090] The rest of the preparation methods and parameters were the same as those in Example 3.

[0091] Example 5

[0092] The difference between this embodiment and embodiment 3 is that 3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate is replaced by 2,2,3,3,4,4,4-heptafluorobutyl methacrylate.

[0093] The rest of the preparation methods and parameters were the same as those in Example 3.

[0094] Example 6

[0095] The difference between this embodiment and embodiment 1 is that the mass ratio of the pure acrylate polymer to the modified acrylate polymer is 50:50.

[0096] The rest of the preparation methods and parameters were the same as those in Example 1.

[0097] Example 7

[0098] The difference between this embodiment and embodiment 1 is that the mass ratio of the pure acrylate polymer to the modified acrylate polymer is 95:5.

[0099] The rest of the preparation methods and parameters were the same as those in Example 1.

[0100] Example 8

[0101] The difference between this embodiment and embodiment 1 is that, based on the total weight of the gel polymer composite electrolyte being 100%, the weight fraction of the lithium salt-containing electrolyte is 99%, and the total weight fraction of the pure acrylate polymer and the modified acrylate polymer is 1%.

[0102] The rest of the preparation methods and parameters were the same as those in Example 1.

[0103] Example 9

[0104] The difference between this embodiment and embodiment 1 is that, based on the total weight of the gel polymer composite electrolyte being 100%, the weight fraction of the lithium salt-containing electrolyte is 45%, and the total weight fraction of the pure acrylate polymer and the modified acrylate polymer is 55%.

[0105] The rest of the preparation methods and parameters were the same as those in Example 1.

[0106] Example 10

[0107] The difference between this embodiment and embodiment 1 is that the mass ratio of the fluorine-containing acrylate polymer to the nitrogen-containing acrylate polymer is 45:55.

[0108] The rest of the preparation methods and parameters were the same as those in Example 1.

[0109] Embodiment 11

[0110] The difference between this embodiment and embodiment 1 is that the mass ratio of the fluorine-containing acrylate polymer to the nitrogen-containing acrylate polymer is 98:2.

[0111] The rest of the preparation methods and parameters were the same as those in Example 1.

[0112] Comparative Example 1

[0113] The difference between this comparative example and Example 1 is that the gel polymer composite electrolyte does not contain modified acrylate polymer.

[0114] The rest of the preparation methods and parameters were the same as those in Example 1.

[0115] Comparative Example 2

[0116] The difference between this comparative example and Example 2 is that the gel polymer composite electrolyte does not contain modified acrylate polymer.

[0117] The rest of the preparation methods and parameters were the same as those in Example 2.

[0118] Comparative Example 3

[0119] The difference between this comparative example and Example 3 is that the gel polymer composite electrolyte does not contain modified acrylate polymer.

[0120] The rest of the preparation methods and parameters were the same as those in Example 3.

[0121] Comparative Example 4

[0122] The difference between this comparative example and Example 1 is that the flexible PAN nanofiber skeleton is replaced by a PP diaphragm.

[0123] The rest of the preparation methods and parameters were the same as those in Example 1.

[0124] Performance Testing

[0125] 1. The thermal stability test of the gel polymer composite electrolyte provided in the above embodiments and comparative examples is carried out. The specific steps include: placing a flexible PAN nanofiber skeleton or a PP separator into the positive electrode shell, and then dropping 200 μL of the prepolymerization solution. After polymerization, the area of ​​the gel electrolyte is calculated at room temperature 25°C, and then placed at 120°C for 2h, and its shrinkage is observed and the area is calculated at the same time, and the area ratio is recorded.

[0126] 2. The polymerization test was performed on the prepolymerization solutions provided in the above embodiments and comparative examples. The specific steps included: allowing the prepolymerization solution to stand at room temperature of 25°C for 12 hours, then polymerizing at 60°C for 12 hours, then tilting the loaded glass bottle at 45° to observe whether there was solution flow.

[0127] 3. Oxidative decomposition potential test: the test method is: assemble a Li / gel polymer composite electrolyte / stainless steel sheet battery with Li as the reference electrode and counter electrode and stainless steel sheet as the working electrode, and use the ZIVE SP1 electrochemical workstation to measure the electrochemical window of the composite electrolyte film by linear sweep voltammetry; test conditions: 2-6V voltage range, scan rate of 1mV / s.

[0128] 4. Ionic conductivity test, the test method is: assemble a symmetrical battery of stainless steel sheet / gel polymer composite electrolyte / stainless steel sheet structure, and use ZIVE SP1 electrochemical workstation to measure the ionic conductivity of the gel polymer electrolyte through electrochemical AC impedance test. The test conditions are as follows: the AC impedance test is carried out in the frequency range of 0.01-1MHz, with an amplitude of 10mV, at room temperature, and the AC impedance experimental results are fitted by ZView software; the ionic conductivity of the gel polymer composite electrolyte is calculated using the conductivity formula: σ=d / RS, where σ represents the ionic conductivity of the gel polymer composite electrolyte, d represents the thickness of the gel polymer composite electrolyte, R represents the bulk impedance value of the fitted gel polymer composite electrolyte, and S represents the effective contact area between the stainless steel sheet and the gel polymer composite electrolyte.

[0129] 5. The electrochemical performance of the lithium-ion batteries provided in the above embodiments and comparative examples was tested. The test conditions were as follows: a constant current charge-discharge cycle test was performed at a rate of 0.5C in the voltage range of 2.4-4.0V using a CT2001A charge-discharge tester (1C=170mAh / g). The test temperature was room temperature (25±2°C).

[0130] The above test results are shown in Table 1.

[0131] Table 1

[0132]

[0133]

[0134] analyze:

[0135] As can be seen from the above table, the present invention uses a nanofiber skeleton as the main body, and cross-links pure polymerized acrylate polymer and modified acrylate polymer on the skeleton, thereby improving the high-voltage resistance of the gel polymer composite electrolyte, improving thermal stability and interface compatibility, and generating a stable electrode / electrolyte interface to increase battery life. In addition, the use of halogen-containing acrylate polymer and nitrogen-containing acrylate polymer is conducive to the formation of lithium halide and lithium nitride on the electrolyte surface, thereby inhibiting the generation of lithium dendrites and improving conductivity and the migration number of lithium ions.

[0136] It can be seen from Examples 1-3 and Comparative Examples 1-3 that the coordination of acrylate polymer and modified acrylate polymer can increase the oxidation decomposition potential, and the discharge capacity at 0.5C is also improved.

[0137] It can be seen from Examples 1 and 3 that the combination of different acrylate polymers and modified acrylate polymers will affect the oxidative decomposition potential, ionic conductivity and electrochemical properties of the gel electrolyte, and the characteristics of different acrylate monomers also need to be considered during the combination.

[0138] It can be seen from Example 1 and Comparative Example 4 that the thermal stability of the flexible PAN nanofiber skeleton prepared by electrospinning is significantly improved compared with the PP diaphragm, and the selected pure acrylate polymer and modified acrylate polymer have excellent thermal stability on the flexible PAN nanofiber skeleton, and do not break or deform after repeated bending, and have good flexibility.

[0139] It can be seen from Examples 3 and 4-5 that the cross-linking polymerization of dipentaerythritol pentaacrylate, 2,2,3,3,4,4,4-heptafluorobutyl methacrylate and ethyl α-cyano-β-(2-furyl) acrylate has a better effect, the oxidative decomposition potential is 5.02 V, and the discharge capacity at 0.5C is 152.4 mAh / g, indicating that 2,2,3,3,4,4,4-heptafluorobutyl methacrylate has a better effect at this ratio, and other fluorine-containing acrylate polymers need to adjust the ratio with pure acrylate polymers to obtain better performance.

[0140] It can be seen from Examples 1 and 6-7 that if the weight ratio of the acrylate polymer to the fluorine-containing acrylate polymer is too small, too much fluorine-containing acrylate polymer is added, resulting in the inability to polymerize into a gel electrolyte. This is mainly because the electronegativity of fluorine atoms is relatively high, which weakens the interaction between polymer chains; if the weight ratio of the acrylate polymer to the fluorine-containing acrylate polymer is relatively large, that is, there are too few acrylate polymers containing modified groups, resulting in poor electrochemical performance and an inappropriate ratio.

[0141] It can be seen from Example 1 and Examples 8-9 that if the electrolyte containing lithium salt is too much, the thermal stability of the formed condensed electrolyte is poor, and the excess electrolyte causes the ion conduction path inside the battery to become complicated, thereby hindering the normal migration of lithium ions and deteriorating the electrochemical performance; if too much pure acrylate polymer and modified acrylate polymer are added, the pore structure and ion channels inside the gel will become tighter and more complex, and the ion conductivity will be hindered, which will increase the internal resistance of the battery and deteriorate the electrochemical performance.

[0142] It can be seen from Examples 1 and 10-11 that if the mass ratio of the fluorine-containing acrylate polymer to the nitrogen-containing acrylate polymer is too small, the excessive nitrogen-containing functional groups will react with the lithium salt in the electrolyte to generate compounds insoluble in the electrolyte, thereby affecting the ionic conductivity of the electrolyte and reducing the electrochemical performance; if the mass ratio of the fluorine-containing acrylate polymer to the nitrogen-containing acrylate polymer is too large, the capacity will decrease due to the poor uniformity of lithium deposition, but the electrical conductivity and redox potential will increase due to the greater amount of lithium fluoride.

[0143] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A gel polymer composite electrolyte, characterized in that: The gel polymer composite electrolyte comprises a nanofiber skeleton, an electrolyte containing a lithium salt, a pure acrylate polymer and a modified acrylate polymer; Wherein, the modified acrylic ester polymer is a combination of a halogen-containing acrylic ester polymer and a nitrogen-containing acrylic ester polymer.

2. The gel polymer composite electrolyte according to claim 1, characterized in that: The material of the nanofiber skeleton includes any one or a combination of at least two of polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, polyvinyl chloride, polyethylene oxide or silicon dioxide, preferably polyacrylonitrile; Preferably, the thickness of the nanofiber skeleton is 20-100 μm; Preferably, in the lithium salt-containing electrolyte, the lithium salt includes any one of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate or lithium dioxalatoborate, or a combination of at least two thereof; Preferably, in the lithium salt-containing electrolyte, the solvent includes any one of ethylene carbonate, dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate, or a combination of at least two of them.

3. The gel polymer composite electrolyte according to claim 1 or 2, characterized in that: The acrylate polymer includes any one or a combination of at least two of polyethylene glycol diacrylate, bisphenol A ethoxylated acid diacrylate, dipentaerythritol pentaacrylate, methacrylate polyethylene glycol methacrylate, polydipentaerythritol hexaacrylate or bisphenol A propylene glycol dimethacrylate, preferably any one or a combination of at least two of polyethylene glycol diacrylate, bisphenol A ethoxylated acid diacrylate or dipentaerythritol pentaacrylate.

4. The gel polymer composite electrolyte according to any one of claims 1 to 3, characterized in that: The mass ratio of the pure acrylate polymer to the modified acrylate polymer is (60-99):(1-40), preferably (70-95):(5-30); Preferably, the halogen-containing acrylate polymer includes a fluorine-containing acrylate polymer and / or a bromine-containing acrylate polymer; preferably, the fluorine-containing acrylate polymer includes any one of 3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl acrylate, (perfluorocyclohexyl) methacrylate, 2-(perfluorooctyl) ethyl methacrylate, 1H,1H,11H-perfluoroundecyl methacrylate, 2,2,3,3,3-pentafluoropropyl acrylate or 2,2,3,3,4,4,4-heptafluorobutyl methacrylate, or a combination of at least two thereof; Preferably, the bromine-containing acrylate polymer comprises poly(pentabromobenzyl acrylate); Preferably, the nitrogen-containing acrylate polymer comprises ethyl α-cyano-β-(2-furyl) acrylate; Preferably, the mass ratio of the halogen-containing acrylate polymer to the nitrogen-containing acrylate polymer is (50-95):(5-50), preferably (70-90):(10-30).

5. The gel polymer composite electrolyte according to any one of claims 1 to 4, characterized in that: Based on the total weight of the gel polymer composite electrolyte being 100%, the weight fraction of the electrolyte containing the lithium salt is 50-99%, preferably 70-95%; Preferably, based on 100% of the total weight of the gel polymer composite electrolyte, the total weight fraction of the pure acrylate polymer and the modified acrylate polymer is 1-50%, preferably 5-30%.

6. A method for preparing a gel polymer composite electrolyte according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (a) mixing an electrolyte containing a lithium salt, a pure acrylate polymer, a modified acrylate polymer and an initiator to obtain a prepolymerization solution; (b) mixing the prepolymer solution and the nanofiber skeleton, and performing an in-situ polymerization reaction to obtain the gel polymer composite electrolyte.

7. The preparation method according to claim 6, characterized in that: The concentration of the lithium salt-containing electrolyte in step (a) is 0.5-2 mol / L; Preferably, the initiator in step (a) comprises any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate or a combination of at least two thereof, preferably azobisisobutyronitrile; Preferably, based on the total weight of the pure acrylate polymer and the modified acrylate polymer as 100%, the weight fraction of the initiator is 0.2-1.2%; Preferably, the mixing process in step (a) is accompanied by stirring.

8. The preparation method according to claim 6 or 7, characterized in that: The preparation method of the nanofiber skeleton in step (b) comprises an electrospinning method; Preferably, in the electrospinning method, the weight ratio of the solute in the electrospinning solution to the solvent is 5-15%; Preferably, the specific parameters of the electrospinning method include: The distance between the spinneret and the grounded collector was 15-25 cm, the applied voltage was 10-25 KV, and the feed rate of the electrospinning solution was 0.3-0.8 mm / h; Preferably, the temperature of the in-situ polymerization in step (b) is 50-70° C. and the time is 6-15 hours.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The preparation method comprises the following steps: (1) A flexible nanofiber skeleton with a thickness of 20-100 μm is prepared as a base membrane by an electrospinning method, and the specific parameters include: The distance between the spinneret and the grounded collector was 15-25 cm, the applied voltage was 10-25 KV, and the feed rate of the electrospinning solution was 0.3-0.8 mm / h; (2) under stirring conditions, adding pure acrylate polymer and modified acrylate polymer to an electrolyte containing lithium salt to obtain a mixed solution, then adding an initiator, and continuing to stir to obtain a prepolymer solution; wherein the mass fraction of the initiator is 0.2-1.2% based on the total weight of the pure acrylate polymer and the modified acrylate polymer as 100%; and the mass ratio of the pure acrylate polymer to the modified acrylate polymer is (60-99):(1-40); (3) adding the prepolymer solution dropwise to the flexible nanofiber skeleton in step (1) to wet it, and then placing it at 50-70° C. for 6-15 hours to carry out an in-situ polymerization reaction to obtain the gel polymer composite electrolyte.

10. A secondary lithium battery, characterized in that: The secondary lithium battery comprises the gel polymer composite electrolyte as claimed in any one of claims 1 to 5.